FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDOENSIA - IGNES JANUAR CAHYADI; DAVID STEVANUS ALANDRI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The objective of this research is to analyze factors that influence firm value of manufacture companies listed in Indonesia Stock Exchange. Those factors are board size, board composition, board meeting, firm size, firm age, managerial ownership, audit committee, profitability, leverage. Population of this research is manufacture companies which are consistently listed in Indonesia Stock Exchange from 2014 to 2016. The period of this study are 2014 until 2016. Samples are obtained through purposive sampling method, in which only 33 of listed manufacture companies in Indonesia Stock Exchange meet the sampling criterias, resulting 99 firm-year observations used in this research. Multiple regression and hypotheses testing are used as the data analysis method in this research. The result of this research show that firm age, audit committee, profitability, leverage have influence on firm value, whereas board size, board composition, board meeting, firm size, managerial ownership do not have influence on firm value